Assessing spatial and trophic segregation between neighbouring colonies of a marine top predator in a upwelling system - Marques, Ana Mafalda de Castro Reis (2019)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia